PENYULUHAN TENTANG PENERAPAN GIZI SEIMBANG PADA TATANAN RUMAH TANGGA DI DESA SEI KAMAH I KEC. SEI DADAP KABUPATEN ASAHAN TAHUN 2023 - lubis, fitri handayani; Sembiring, Bungamari (Jurnal Pengabdian Masyarakat Putri Hijau, 2024)
Initial survey data shows that housewives have not implemented a balanced nutrition program in their households, such as consuming a varied diet, reducing salt and sugar, and some even rarely consume vegetables and fruit. This activity was carried out in Sei Kamah I Village, District. Sei Dadap Asahan Regency in September 2023. All participants who attended consisted of various family members from children, mothers, fathers and even grandfathers and grandmothers attended enthusiastically taking part in outreach activities regarding the application of balanced nutrition in the household setting.